Modification of RC Car Design for Automotive Vehicle Application - Baharuddin, Muhammad Haziq Aiman; Darlis, Nofrizalidris; Syabillah Sulaiman (Progress in Engineering Application and Technology, 2025)
The rapid advancement of technology has revolutionised various aspects of human life, notably in transportation. The transition to AVs represents a paradigm shift, promising to redefine mobility as we know it. High development expenses arise from the need for advanced hardware, such as sensors and processors, sophisticated software systems, and extensive testing. Building a real autonomous car is not an easy task. From a design perspective, autonomous RC vehicles frequently employ techniques like computer vision, machine learning, and path-planning algorithms to read sensor data and decide how to steer, accelerate, and brake in response to the surroundings. The limited space of RC cars also needs to be highlighted. This project aims to construct a design that can assemble all components and sensors in an RC car and ensure the autonomous RC car can function and move without human help. The method used by screening is to reduce the many product concept ideas generated to a relative few that will get additional refinement and analysis. The scoring method is used to rank or prioritize options based on specific criteria or metrics for the autonomous RC car. The design for the bumper and bracket that have the highest scoring score will be printed and mounted into the RC car. After the sensor and component have been coded, the RC car can autonomously move without human intervention.